Reconstruction of large segmental bone defects in rabbit using the Masquelet technique with α-calcium sulfate hemihydrate - Meng, Zhu Long; Wu, Zi Quan; Shen, Bi Xin; Li, Hong Bo; Bian, Yang Yang; Zeng, De Lu; Fu, Jian; Peng, Lei (Journal of orthopaedic surgery and research, 2019)
Background Large segmental bone defects can be repaired using the Masquelet technique in conjunction with autologous cancellous bone (ACB). However, ACB harvesting is severely restricted. α-calcium sulfate hemihydrate (α-CSH) is an outstanding bone substitute due to its easy availability, excellent biocompatibility, biodegradability, and osteoconductivity. However, the resorption rate of α-CSH is too fast to match the rate of new bone formation. The objective of this study was to investigate the bone repair capacity of the Masquelet technique in conjunction with isolated α-CSH or an α-CSH/ACB mix in a rabbit critical-sized defect model. Methods The rabbits ( n = 28) were randomized into four groups: sham, isolated α-CSH, α-CSH/ACB mix, and isolated ACB group. A 15-mm critical-sized defect was established in the left radius, followed by filling with polymethyl methacrylate spacer. Six weeks after the first operation, the spacers were removed and the membranous tubes were grafted with isolated α-CSH, isolated ACB, α-CSH/ACB mix, or none. Twelve weeks later, the outcomes were evaluated by manual assessment, radiography, and spiral-CT. The histopathological and morphological changes were examined by H&E staining. The levels of alkaline phosphatase and osteocalcin were analyzed by immunohistochemistry and immunofluorescence staining. Results Our results suggest that the bone repair capacity of the α-CSH/ACB mix group was similar to the isolated ACB group, while the isolated α-CSH group was significantly decreased compared to the isolated ACB group. Conclusion These results highlighted a promising strategy in the healing of large segmental bone defect with the Masquelet technique in conjunction with an α-CSH/ACB mix (1:1, w / w ) as they possessed the combined effects of sufficient supply and low resorption.